Bibliometrics of Social Mobility Studies in the Digital Age - Judijanto, Loso; Haryanti, Titik (Eastasouth Institute, 2025)
This bibliometric study explores the evolution and thematic landscapes of social mobility research within the digital age, drawing on an extensive dataset derived from the Scopus database from 2000 to 2025. We conducted a comprehensive analysis to identify significant trends, collaboration patterns, and emerging themes in the literature. Our findings highlight the enduring relevance of traditional factors such as education, income, and occupation in discussions of social mobility, while also pointing to the growing importance of digital literacy and access. The study reveals a dynamic field characterized by robust international collaborations, with a notable increase in contributions from non-Western countries. Additionally, the analysis suggests significant gaps, particularly concerning the long-term effects of digital technologies on social mobility and the integration of mental health factors. These insights are crucial for informing policy and future research directions, ensuring that advancements in digital technology foster rather than hinder social mobility.